Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
In the 23rd year his income was of $33,900.
Step-by-step explanation:
Joe's income has been increasing each year by the same dollar amount.
This means that his salary after t years is given by:
[tex]S(t) = S(0) + at[/tex]
In which S(0) is the initial salary and a is the yearly increase.
The first year his income was $22,000
This means that [tex]S(0) = 22000[/tex]. So
[tex]S(t) = S(0) + at[/tex]
[tex]S(t) = 22000 + at[/tex]
In the fourth year his income was $24,100
S(4) = 24100, and thus, we use this to find a.
[tex]S(t) = 22000 + at[/tex]
[tex]24100 = 22000 + 4a[/tex]
[tex]4a = 2100[/tex]
[tex]a = \frac{2100}{4}[/tex]
[tex]a = 525[/tex]
So
[tex]S(t) = 22000 + 525t[/tex]
In which year was his income 33,900
This is t for which S(t) = 33900. So
[tex]S(t) = 22000 + 525t[/tex]
[tex]33900 = 22000 + 525t[/tex]
[tex]525t = 11900[/tex]
[tex]t = \frac{11900}{525}[/tex]
[tex]t = 22.67[/tex]
Rounding up, in the 23rd year his income was of $33,900.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.